(12x*4x)*2x=56

Simple and best practice solution for (12x*4x)*2x=56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12x*4x)*2x=56 equation:


Simplifying
(12x * 4x) * 2x = 56

Reorder the terms for easier multiplication:
(12 * 4x * x) * 2x = 56

Multiply 12 * 4
(48x * x) * 2x = 56

Multiply x * x
(48x2) * 2x = 56

Remove parenthesis around (48x2)
48x2 * 2x = 56

Reorder the terms for easier multiplication:
48 * 2x2 * x = 56

Multiply 48 * 2
96x2 * x = 56

Multiply x2 * x
96x3 = 56

Solving
96x3 = 56

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '96'.
x3 = 0.5833333333

Simplifying
x3 = 0.5833333333

Reorder the terms:
-0.5833333333 + x3 = 0.5833333333 + -0.5833333333

Combine like terms: 0.5833333333 + -0.5833333333 = 0.0000000000
-0.5833333333 + x3 = 0.0000000000

The solution to this equation could not be determined.

See similar equations:

| 4k-1/2=42 | | 24x+3x+11=308 | | 48*2x=56 | | -8.2c=-3.69 | | 130x+110x= | | 48x=56 | | 7x+18=8x | | k-/-2=7 | | 1.25/.25 | | 5x-11=7x+2 | | 1.125/.25 | | 9u-8=92 | | 8k2/4k4 | | 2x+7y=26.10 | | .7x^2+3.2x+1.5=0 | | (3y^2-y-4)+(2y^2-6y+7)= | | 4/5c=12/25 | | 2x-6x+4=24 | | 48x^2=56 | | 7p-5=4p-17 | | 53-12x+21+3x-14+39x=0 | | 1.6y=y+3 | | -5x-75=10x | | 1=k+n | | -18+2x=17-3x | | 12-10t=25+3t | | 24x^3y^5z+48xy^3z^4+0=0 | | -5c-7=-3c-7 | | -10(q-7)+1=1 | | -5+x=4-2x | | 4x-(3x-36)+1=10 | | 3x+6+5x=22 |

Equations solver categories